Inovasi Pendidikan Wirausaha Sosial, Upaya Pemberdayaan Masyarakat (Studi Kasus Implementasi Inovasi Pendidikan Wirausaha Sosial Melalui Pelatihan Pembuatan Sabun Alami) - Hastalona, Dina; meliza, juli (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
The integration of practical experience, interdisciplinary approaches, and the cultivation of an entrepreneurial mindset are important components in the evolution of social entrepreneurship education. The aim of writing this article is to determine the improvement in the quality of training through social entrepreneurial innovation and the availability of resources as an effort to empower the community (case study of the implementation of social entrepreneurial educational innovation through natural soap making training). This activity involves several campuses and prospective entrepreneurs from the East Medan Village Women's group, held at the East Medan Village PKK park on Tuesday 14 May 2024, from 08.00 to 08.00. finished. Activities carried out begin with providing theory followed by direct practice on the spot.   The results obtained are proven educational innovation through innovative training, practical experience such as making natural soap, and a comprehensive understanding of the principles of social entrepreneurship can enrich social entrepreneurship education. By implementing this approach, educational institutions can empower students or prospective entrepreneurs to become effective agents of change in overcoming complex social and environmental challenges.